Attenuation of exercise induced asthma by local hyperthermia. Issue 8 (August 1992) - Johnston, S L; Perry, D; O'Toole, S; Summers, Q A; Holgate, S T
Abstract : BACKGROUND: Prior treatment with local hyperthermia has been shown to prevent mast cell degranulation and leucocyte histamine release, and to reduce mortality and cellular infiltrates in a model of acute lung injury. Local hyperthermia is effective in reducing the symptoms of the common cold and perennial and seasonal allergic rhinitis, nasal patency also being improved in rhinitis. It is possible that these effects are mediated by common anti-inflammatory mechanisms, and that this treatment may be effective in the treatment of asthma. The effect of prior local hyperthermia on the response to exercise challenge and histamine bronchoprovocation was therefore examined. METHODS: In a randomised, double blind, placebo controlled, crossover study, 10 asthmatic subjects with exercise induced asthma used machines delivering 40 1/minute of fully humidified air at either 42 degrees C (active treatment) or 31 degrees C (placebo treatment) for 30 minutes' tidal breathing. For each pretreatment, at two week intervals they underwent exercise challenges starting one and 24 hours after starting the inhalations. After a further two weeks the protocol was repeated with histamine substituted for the exercise challenges. RESULTS: The mean (SE) maximum percentage fall in forced expiratory volume in one second (FEV1) was significantly lower one hour after treatment with air at 42 degrees C (30.8% (3.1%)) than after treatment with air at 31 degrees C (22.3% (2.9%)). There was no significant effect on exercise challenge at 24 hours, or on histamine challenge at either time point, though there were nonsignificant trends towards protection with exercise at 24 hours and with histamine at one hour. CONCLUSION: In asthmatic subjects the response to exercise challenge is significantly attenuated one hour after treatment with local hyperthermia. This treatment warrants further investigation in the treatment of clinical asthma and other inflammatory disorders.